2021
DOI: 10.2478/prilozi-2021-0001
|View full text |Cite
|
Sign up to set email alerts
|

Insight in the Current Progress in the Largest Clinical Trials for Covid-19 Drug Management (As of January 2021)

Abstract: The outbreak of the COVID-19 pandemic has generated the largest global health crisis of the 21st century, evolving into accelerating socioeconomic disruption. In spite of all rapidly and widely emerging scientific data on epidemiology, diagnosis, prevention and treatment of the COVID-19 disease, severe acute respiratory coronavirus 2 (SARS-CoV-2) is continuing to propagate in lack of definitive and specific therapeutic agents. Current therapeutic strategies are mainly focused on viral inhibition by antiviral d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Therefore, the need for a clear understanding of immunopathological factors underpinning the diverse responses observed in the infected patients is of paramount significance to identify appropriate therapeutic targets [ 21 ]. Several immunomodulatory agents are currently underpinning clinical trials at a rapid pace [ 22 ], and some of them are already being under routine use in the clinical practices in off-label use of drugs [ 23 ]. An in-depth understanding of each specific inflammatory pathway and cell-type shows promising results in choosing appropriate immunotherapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the need for a clear understanding of immunopathological factors underpinning the diverse responses observed in the infected patients is of paramount significance to identify appropriate therapeutic targets [ 21 ]. Several immunomodulatory agents are currently underpinning clinical trials at a rapid pace [ 22 ], and some of them are already being under routine use in the clinical practices in off-label use of drugs [ 23 ]. An in-depth understanding of each specific inflammatory pathway and cell-type shows promising results in choosing appropriate immunotherapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…The study by the ACTT-1 Study Group Members demonstrated a 31 % faster recovery (11 days with remdesivir in comparison to 15 days with placebo) and a survival advantage of 7.1% mortality with remdesivir versus 11.9 % mortality with placebo (although statistically insignificant regarding mortality). Following the preliminary findings of the remdesivir ACTT-1 Trial conducted by the American National Institute of Allergy and Infectious Diseases (NIAID) [12][13][14] , the Food and Drug Administration (FDA) in the United States of America (USA) issued an Emergency Use Authorization (EUA) licensing use of remdesivir for treatment of adults and children hospitalized with verified or suspected COVID-19 infection. This authorization was modified on August 28, 2020, expanding use of remdesivir to all hospitalized patients regardless of the severity of the clinical condition.…”
Section: Favipiravir and Remdesivirmentioning
confidence: 99%